SARS-CoV-2 Associated Respiratory Failure in a Preterm Infant and the Outcome after Remdesivir Treatment. Issue 5 (8th April 2022) - Sarhan, Mohammed A.; Casalino, Maria; Paopongsawan, Pongsatorn; Gryn, David; Kulkarni, Tapas; Bitnun, Ari; Gauda, Estelle B.
Abstract : Severe coronavirus disease 2019 (COVID-19) occurs in approximately 10% of neonates infected with severe acute respiratory syndrome coronavirus 2. Guidelines for optimal management of severe COVID-19 in neonates do not exist. In this report, we describe a late-preterm neonate with severe COVID-19, requiring invasive mechanical ventilation who recovered following treatment with remdesivir and high dose dexamethasone.